2023
DOI: 10.5194/acp-23-4637-2023
|View full text |Cite
|
Sign up to set email alerts
|

Yields and molecular composition of gas-phase and secondary organic aerosol from the photooxidation of the volatile consumer product benzyl alcohol: formation of highly oxygenated and hydroxy nitro-aromatic compounds

Abstract: Abstract. Recently, volatile chemical products (VCPs) have been increasingly recognized as important precursors for secondary organic aerosol (SOA) and ozone in urban areas. However, their atmospheric chemistry, physical transformation, and impact on climate, environment, and human health remain poorly understood. Here, the yields and chemical composition at the molecular level of gas- and particle-phase products originating from the photooxidation of one of these VCPs, benzyl alcohol (BnOH), are reported. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
2
1
0
Order By: Relevance
“…As found in other systems, epoxides can effectively lead to SOA formation (Paulot et al, 2009;Chan et al, 2010). Other fragmentation products found in Jaoui et al also suggest that fragmentation products can form with high O:C ratios and may quickly partition to SOA (Jaoui et al, 2023). Here, we detect products with masses congruent with both the hydroxy oxopentenal and epoxide products.…”
Section: Fragmentation and Ring-opening Productssupporting
confidence: 85%
See 2 more Smart Citations
“…As found in other systems, epoxides can effectively lead to SOA formation (Paulot et al, 2009;Chan et al, 2010). Other fragmentation products found in Jaoui et al also suggest that fragmentation products can form with high O:C ratios and may quickly partition to SOA (Jaoui et al, 2023). Here, we detect products with masses congruent with both the hydroxy oxopentenal and epoxide products.…”
Section: Fragmentation and Ring-opening Productssupporting
confidence: 85%
“…A previous study of the chemical composition of the SOA formed via OH oxidation of benzyl alcohol observed C6 compounds, such as nitrocatechol (Charan et al, 2020;Jaoui et al, 2023). In the present study, we observed nitrocatechol as well as other C6 compounds such as phenol and catechol.…”
Section: C6 Compoundssupporting
confidence: 74%
See 1 more Smart Citation